Sterigmatocystin production by Aspergillus nidulans - K. R. Branch; J. W. Bennett; D. Bhatnagar (Fungal Genetics Reports, 1993)
Sterigmatocystin (ST), a mycotoxin with the molecular formula C18 H12 O6, is reported from seven genera of fungi, including 22 species of Aspergillus (Cole and Cox 1981 Handbook of Toxic Fungal Metabolites, Academic Press pp 67-93).